Nitrate repletion during spring bloom intensifies phytoplankton iron demand in Yangtze River tributary, China. (September 2020) - Nwankwegu, Amechi S.; Li, Yiping; Huang, Yanan; Wei, Jin; Norgbey, Eyram; Ji, Daobin; Pu, Yashuai; Nuamah, Linda A.; Yang, Zhengjian; Jiang, Yufeng; Paerl, Hans W.
Abstract: Most aquatic systems show characteristic seasonal fluctuations in the total nutrient pool supporting primary productivity. The nutrient dynamics essentially exacerbate critical demand for the counterpart micronutrients towards achieving ecosystem equilibrium. Herein, the phytoplankton demand for iron (Fe) uptake under high concentration of nitrate-nitrogen during spring in Xiangxi Bay, China, was studied. Our result confirmed that significant Fe concentrations (P = 0.01) in both autumn (0.62 ± 0.02 mgL −1 ) and winter (0.06 ± 0.03 mgL −1 ) relative to spring (0.004 ± 0.01 mgL −1 ) are linked to the low NO3 − N paradigms during autumn and winter. As NO3 − N showed a sharp increase in spring, a dramatic reduction in the Fe pool was observed in the entire tributary, driving the system to a critical Fe limited condition. Bioassay study involving Fe additions both alone and in combinations led to maximum growth stimulation with biomass as chla (16.44 ± 0.82 μgL −1 ) and phytoplankton cell density (6.75 × 10 6 cellsL −1 ) which differed significantly (P = 0.03) with the control. Further, the study demonstrated that Fe additions triggered biomass productions which increased linearly with cell densities. The P alone addition caused biomass production (15.26 ± 2.51 μgL −1 ) greater than both NO3 − N (9.15 ± 0.66 μgL −1 ) and NH4 + N (13.65 ± 1.68 μgL −1 ) separate additions but reported a low aggregate cell density (3.18 × 10 6 cellsL −1 ). This indicates that nutrient and taxonomic characteristics e.g., high cell pigment contents rather than just the cell bio-volume also determine biomass. The Bacilliarophyta, Chlorophyta, and Cryptophyta with the total extinction of Cyanophyta characterized the bloom in spring. The anthropogenic NO3 − N input into XXB would have driven to higher NO3 − N than NH4 + N situation, and incapacitated the Cyanophyta that preferentially utilize NH4 + N. Our study provides a useful report for incorporation into the monitoring programs for prudent management of phytoplankton bloom and pollution across the eutrophic systems. Graphical abstract: Image 1 Highlights: The Xiangxi Bay (XXB) shows temporal fluctuations in nutrient concentrations across seasons. A holistic Fe limitation driven by NO3 − N repletion characterizes spring bloom in XXB. Bioassay involving Fe addition stimulates biomass which increases linearly with the phytoplankton cell density. The Bacilliarophyta, Chlorophyta, and Cryptophyta actively control the XXB spring bloom. The Cryptophyta dominated by Chroomonas acuta overwhelm other phytoplankton taxa during spring in XXB.